Resolution of Social Conflicts Through Multicultural Education - T Heru Nurgiansah; Medita Ayu Wulandari; Cici Fitri Bety (JED (Jurnal Etika Demokrasi), 2022)
The purpose of this research is to analyze multicultural education as a solution to resolve social conflicts among students. The method used in this study is qualitative with data collection techniques through observation, interview, and documentation. Multicultural education offers an alternative through the application of educational strategies and concepts based on the utilization of diversity in society, especially those among students such as ethnic diversity, culture, language, religion, social status, gender, ability, age, and race. An approach through multicultural education is important. The education strategy is not only aimed at making it easy for students to understand the courses they are studying, but also to raise their awareness to always behave humanist, pluralist, and democratic. The results showed that Multicultural Education that has been applied in National education is expected to be an agent in the community that bridges the game in the midst of plurality, this can be seen from the substance contained in multicultural education that prioritizes attitudes and principles on democracy, equality, and justice, oriented to humanity, togetherness, and peace. Develop an attitude of recognizing, accepting, and appreciating cultural diversity. With this function, SARA conflict can be prevented.